Changing Demographics and Human Capital Development: Implications for Economic Growth in Nigeria - Campbell, Omolara A; Okuwa, Oluwakemi B (Archives of Business Research, 2016)
The three major drivers of demographic trends are fertility, mortality and immigration. The demographic position in Nigeria has changed in recent years with crude birth and death rates as well as fertility rates falling. As countries move through demographic trends, the size of the working age population increases. Such outcomes have economic consequences, which lead to increase in aggregate income level through expected increase in productivity level. This paper investigates the channels through which human capital development could stimulate economic growth during changing demographics. In our model, the growth of the economy is a function of productivity and productivity itself is a function of demographic trends. Thus, a Two-Stage Least Squares (2SLS) econometric technique was adopted. Our result shows that productivity and investment in education has an elastic impact on the growth of the economy.